Rancang Sistem Deteksi Dini Terjadinya Kebakaran Menggunakan Logika Fuzzy pada Area Parkiran - I Gusti Putu Kresna Dana; Putu Hendra Suputra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
This study discusses the development of a fire monitoring system in a semi-outdoor multi-storey car park by utilizing Internet of Things (IoT) technology. The experimental research method is used with the design science research method (DSRM) stage. The system uses MQ-2, DHT11, and YG-1006 sensors to detect smoke, temperature increases, and flames. Data from the sensors is processed using fuzzy logic to determine the level of danger by the Arduino Uno microcontroller and notifications are forwarded via the LCD display to security officers. The test results show that the system can produce digital values that represent the level of danger based on environmental conditions. The conclusion states that this system has the potential to improve responsiveness and reliability in dealing with fire risks in a semi-outdoor multi-storey car park environment.